Demenca: definicija, oblike in možnosti zdravljenja - Krajnc, Nik (Medicinski razgledi, 2019)
Dementia is a relatively common neurodegenerative disorder, which mainly affects the elderly. It is defined as a progressive syndrome with the impairment of two or more higher cortical functions, which disables patients to normally perform their daily activities. The most common form of dementia is Alzheimer's disease, followed by vascular, Lewy body, frontotemporal, and mixed dementia, other types are seen less often. It is essential to exclude the potentially reversible causes of dementia. In addition to laboratory tests and imaging techniques, we use several screening tests, among which Clock-Drawing Test is most commonly used by general practitioners, whereas Mini Mental State Examination and Montreal Cognitive Assessment are more often used by neurology specialists. Treatment is symptomatic and includes the treatment of cognitive (acetylcholinesterase inhibitors, glutamate N-metyl-D-aspartate receptor agonists) and neuropsychiatric symptoms (antidepressants, antopsychotics), but nevertheless the psychotherapeutic strategies are of great importanceas well.
Keywords: demenca; diagnostika; zdravljenje